COMMUNICATION SKILLS AMONG AGRICULTURAL EXTENSION WORKERS IN NINEVEH GOVERNORATE AND ITS RELATIONSHIP WITH PERSONAL AND VOCATIONAL CHARACTERISTICS - Nabeel Abdel-Maseeh Behnam (Mesopotamia Journal of Agriculture)
The aim of this study was to recognize the communication skills extension workers in Nineveh governorate by limiting their communication skill level .arranging communication skills fields and limiting the relation between communication skills level of extension workers and these personal and vocational characteristics. (level of education. specialization. vocational service period. period of working in extension work. training during service specializing in extension work and attitude toward agricultural extension). The population consisted of all workers of Nineveh agriculture directorate and its divisions . which was 181 workers the sample included 124 workers. Data were collected by a questionnaire which had two parts .the first the contained data related with some personal and vocational characteristics . the second part contained a measurement have many items to limit the level of extension workers communication skills. the data were analyzed by using simple person correlation spearman rank correlation and multiple step- wise regression analysis. The main findings are as follows most of extension workers in Nineveh governorate have medium communication skills which tend to decreasing and also their are a significant relation between the level of communication skills of extension workers and these factors vocational service period .period of working in extension job. training during service. and attitude toward agricultural extension .